2014
DOI: 10.1111/jonm.12233
|View full text |Cite
|
Sign up to set email alerts
|

A study of the determinants of work-to-family conflict among hospital nurses in Belgium

Abstract: To retain and attract nurses by reducing work-to-family conflict, hospitals should not (only) rely on work-family policies but should also invest in organisational support and adapted job dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 80 publications
2
38
1
1
Order By: Relevance
“…This indicated that job demands increased the level of work-life imbalance, regardless of work or personal life. In this regard, the results were in agreement with findings from previous studies (Beham et al 2011, Lembrechts et al 2015. Overall, job demands are a major source of work-life imbalance among RNs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicated that job demands increased the level of work-life imbalance, regardless of work or personal life. In this regard, the results were in agreement with findings from previous studies (Beham et al 2011, Lembrechts et al 2015. Overall, job demands are a major source of work-life imbalance among RNs.…”
Section: Discussionsupporting
confidence: 92%
“…Psychological demands tend to worsen the interference/conflict between work and personal life (Lembrechts et al . ). As such, in contrast to work resources, the presence of job demands is expected to undermine WLE.…”
Section: Overview Of Literature and Hypothesis Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Nursing is considered an inherently demanding occupation. Not only are nurses exposed to a variety of job stressors such as pain and death, high emotional expectations of patients, demanding and nonstandard job schedules and work overload but also often lack adequate resources to deal with these stressors (Allen & Mellor, ; Demerouti, Bakker, Nachreiner, & Schaufeli, ; Lembrechts, Dekocker, Zanoni, & Pulignano, ; Van Bogaert et al, ). In many developing countries, demands on nurses are exacerbated by shortage in the number of nurses due to factors such as ageing, poor salaries and limited career prospects for nurses (Mason, Leavitt, & Chaffee, ; Yildirim & Aycan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, support from management and colleagues were considered. Lembrechts et al (2014) found that physician and co-worker support significantly decreased WFC in nurses, whereas Cortese et al (2010) found that only supportive management was correlated with WFC and not colleagues' support. Yildirim and Yacan (2008) observed that social support from supervisors was directly associated with lower WFC and higher job satisfaction, but not with life satisfaction.…”
Section: Antecedents or Predictors Of Wfcmentioning
confidence: 96%